Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
1x + 4y = 4 ⇒ 6x + 24y = 24
6x - 8y = 0 ⇒ 6x - 8y = 0
32y = 24
32 32
y = 3/4
x + 4(3/4) = 4
x + 3 = 4
-3 -3
x = 1
(x, y) = (1, 3/4)
6x - 8y = 0 ⇒ 6x - 8y = 0
32y = 24
32 32
y = 3/4
x + 4(3/4) = 4
x + 3 = 4
-3 -3
x = 1
(x, y) = (1, 3/4)
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.